2022
DOI: 10.1177/18344909221117257
|View full text |Cite
|
Sign up to set email alerts
|

A network perspective on marital satisfaction among older couples

Abstract: It will be helpful for older people to maintain good mental health by improving their marital satisfaction. The present study investigates how the elements of marital satisfaction among older couples are related to each other and reveal the key elements. Four hundred ninety-four older people participated in the study. Marital satisfaction was assessed by the 10-item marital satisfaction subscale of the ENRICH scale. Network analysis was adopted to estimate the network structure of these 10 items and the streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…This association aligns with the recently proposed sex-as-leisure perspective, which emphasizes that positive sexuality, by connecting sexual behavior and expression to happiness and wellbeing, is consistent with leisure engagement (Berdychevsky and Carr, 2020;Williams et al, 2020). Previous research involving older couples (Li et al, 2022) found a stronger, moderate-to-large connection between nodes EMS10 and EMS11, although in that study, EMS11 exclusively addressed expression of affection, omitting any mention of sexuality. The difference in effect size might be attributable to the different item wording, as in later life stages, non-sexual forms of affection may become more significant (Towler et al, 2023), resulting in a stronger link with partnership facets such as shared activities.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This association aligns with the recently proposed sex-as-leisure perspective, which emphasizes that positive sexuality, by connecting sexual behavior and expression to happiness and wellbeing, is consistent with leisure engagement (Berdychevsky and Carr, 2020;Williams et al, 2020). Previous research involving older couples (Li et al, 2022) found a stronger, moderate-to-large connection between nodes EMS10 and EMS11, although in that study, EMS11 exclusively addressed expression of affection, omitting any mention of sexuality. The difference in effect size might be attributable to the different item wording, as in later life stages, non-sexual forms of affection may become more significant (Towler et al, 2023), resulting in a stronger link with partnership facets such as shared activities.…”
Section: Discussionsupporting
confidence: 84%
“…This is coherent with findings pointing to the positive impact of good communication on the perception of a partner's behaviors and personal characteristics and on conflict resolution, which may ultimately enhance relationship satisfaction (Li et al, 2018;Pagani et al, 2019;Karakose and Ledermann, 2023). Noteworthy, communication and personality issues were connected by the same edge weight in a study of older couples that explored the network of marital satisfaction using the ENRICH marital satisfaction scale (Li et al, 2022). A small-tomoderate edge connected nodes EMS10 ("I am very happy with how we manage our leisure activities and the time we spend together") and EMS11 ("I am very pleased about how we express affection and relate sexuality").…”
Section: Discussionsupporting
confidence: 80%
“…This association aligns with the recently proposed sex-as-leisure perspective, which emphasizes that positive sexuality, by connecting sexual behavior and expression to happiness and well-being, is consistent with leisure engagement ( Berdychevsky and Carr, 2020 ; Williams et al, 2020 ). Previous research involving older couples ( Li et al, 2022 ) found a stronger, moderate-to-large connection between nodes EMS10 and EMS11, although in that study, EMS11 exclusively addressed expression of affection, omitting any mention of sexuality. The difference in effect size might be attributable to the different item wording, as in later life stages, non-sexual forms of affection may become more significant ( Towler et al, 2023 ), resulting in a stronger link with partnership facets such as shared activities.…”
Section: Discussionmentioning
confidence: 79%
“…This is coherent with findings pointing to the positive impact of good communication on the perception of a partner’s behaviors and personal characteristics and on conflict resolution, which may ultimately enhance relationship satisfaction ( Li et al, 2018 ; Pagani et al, 2019 ; Karakose and Ledermann, 2023 ). Noteworthy, communication and personality issues were connected by the same edge weight in a study of older couples that explored the network of marital satisfaction using the ENRICH marital satisfaction scale ( Li et al, 2022 ). A small-to-moderate edge connected nodes EMS10 (“I am very happy with how we manage our leisure activities and the time we spend together”) and EMS11 (“I am very pleased about how we express affection and relate sexuality”).…”
Section: Discussionmentioning
confidence: 99%